2020
DOI: 10.4236/ojst.2020.104007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tooth Surface Loss on the Quality of Life of Patients Seen in a Nigerian Teaching Hospital

Abstract: Background: Tooth surface loss (TSL) is a progressive process arising from erosion, abrasion, attrition or abfraction. It can affect individuals of any age group: children, young adult, adults or the elderly and can compromise the health of individual tooth or the entire dentition leading to poor quality of life of the affected person. Objective: To evaluate the pattern of TSL among dental patients in a Nigerian Teaching Hospital and to assess the impact of TSL on their quality of life. Subjects and Methods: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…With respect to the type of missing teeth (mandibular, maxillary or complete edentulism), a signi cant in uence on quality of life was found (p < 0.000) (Table 1). Similar to the studies of Ogunrinde et al [3] in Nigeria, 47.3% of missing teeth were from the upper jaw, with a statistically signi cant relationship between the location of missing teeth and the severity of the impact on the quality of life of the participants. Batista et al [5] reported a consistent impact on quality of life in Brazilian individuals with the number and position of missing teeth, with a prevalence of 48.1%.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…With respect to the type of missing teeth (mandibular, maxillary or complete edentulism), a signi cant in uence on quality of life was found (p < 0.000) (Table 1). Similar to the studies of Ogunrinde et al [3] in Nigeria, 47.3% of missing teeth were from the upper jaw, with a statistically signi cant relationship between the location of missing teeth and the severity of the impact on the quality of life of the participants. Batista et al [5] reported a consistent impact on quality of life in Brazilian individuals with the number and position of missing teeth, with a prevalence of 48.1%.…”
Section: Discussionsupporting
confidence: 85%
“…While a combined loss of posterior and anterior teeth was observed in patients from 43 to 59 years of age, patients over 60 years of age exhibited greater loss of teeth, with a higher proportion of individuals with complete edentulism and corresponding severe/very severe impact on quality of life (Table 2). In Nigeria, Ogunrinde et al [3] found that the majority (47.3%) of missing teeth were from the upper jaw; almost half of the respondents had missing posterior teeth (49.7%), while 37.5% were missing anterior teeth and 12.7% were missing anterior and posterior teeth. Borda et al Page 10/12 [19] examined edentulism-related quality of life in Ecuador and reported that 77.13% of older adults self-reported fair/poor health depending on the number of missing teeth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over time, this discomfort can worsen, resulting in spontaneous pain or pulp necrosis. Patients usually seek help due to pain, changes in function, and dissatisfaction with their appearance (5). Accurate evaluation of the degree of tooth wear is critical for developing effective interventions, in a study it was noted that TSL typically is symmetrical in both the upper and lower teeth (6).…”
Section: Introductionmentioning
confidence: 99%